The Settlement Organization of Sparta, from the Bronze Age to the Roman Period - Christesen, Paul; Kramer, Nathaniel W. (Classica et Mediaevalia, 2024)
This article presents the results of a research program intended to enhance our knowledge of the realities of the city of Sparta. We have built a spatially enabled database linked to Geographic Information System (GIS) software to compile, analyze, and visualize all the finds from excavations in Sparta that have been treated in excavation reports and other scholarly publications. We are, as a result, in a position to offer a more detailed diachronic history of the settlement organization of Sparta than has heretofore been possible.